2016
DOI: 10.1007/s12026-016-8805-y
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase SHP-1: resurgence as new drug target for human autoimmune disorders

Abstract: Recognition of self-antigen and its destruction by the immune system is the hallmark of autoimmune diseases. During the developmental stages, immune cells are introduced to the self-antigen, for which tolerance develops. The inflammatory insults that break the immune tolerance provoke immune system against self-antigen, progressively leading to autoimmune diseases. SH2 domain containing protein tyrosine phosphatase (PTP), SHP-1, was identified as hematopoietic cell-specific PTP that regulates immune function f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Signal regulatory protein α is enriched in myeloid cells, while its ligand CD47 is universally expressed. Interaction between CD47 and SIRPα induces SHP1/SHP2 activation through tyrosine phosphorylation in the SH2 domains ( 27 , 28 ), leading to inhibited macrophage phagocytosis and pro-inflammatory response. BMDMs from normal mice were transfected with SIRPα siRNA (si-SIRPα) or control oligonucleotide (NC), which were proven to inhibit SIRPα expression efficiently (Figures S2A,B in Supplementary Material), and stimulated with PBS or LPS + IFNγ for 24 h. Western blotting showed that knock-down of SIRPα by siRNA (si-SIRPα) significantly reduced SHP1 phosphorylation in M PBS and M LPS macrophages (Figures 2 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Signal regulatory protein α is enriched in myeloid cells, while its ligand CD47 is universally expressed. Interaction between CD47 and SIRPα induces SHP1/SHP2 activation through tyrosine phosphorylation in the SH2 domains ( 27 , 28 ), leading to inhibited macrophage phagocytosis and pro-inflammatory response. BMDMs from normal mice were transfected with SIRPα siRNA (si-SIRPα) or control oligonucleotide (NC), which were proven to inhibit SIRPα expression efficiently (Figures S2A,B in Supplementary Material), and stimulated with PBS or LPS + IFNγ for 24 h. Western blotting showed that knock-down of SIRPα by siRNA (si-SIRPα) significantly reduced SHP1 phosphorylation in M PBS and M LPS macrophages (Figures 2 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly apparent in motheaten (me) mice that have a spontaneous mutation in Ptpn6, resulting in loss of Shp1, and develop a broad array of inflammatory and autoimmune symptoms. Given the important regulatory function of Shp1 in immune cells, there is growing interest in targeting this phosphatase in autoimmune disease and cancer [1,2]. Indeed, compounds that could enhance Shp1 function may be useful for suppression of immune function [3].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that tyrosine phosphorylation of the ITIMs of Tir may have inhibited intestinal immunity during EDL933 infection. modulate the immune response [ 43,44]. To determine the role of SHP-1 in Tir-mediated inhibition of cytokine production, we transfected RAW264.7 cells with negative control small interfering RNA (siRNA) (NC) or SHP-1-specific siRNA by electroporation ( Figure 7a).…”
Section: Itims Of Ehec Tir Specifically Inhibit Intestinal Immunitymentioning
confidence: 99%